Effect of s/g ratio on kraft pulping and ecf bleaching of some poplars and eucalyptus - Ventorim, Gustavo [UNESP]; Alves, Ericka F.; Penna, Lais S.; Francis, Raymond C. (Editura Acad Romane, 2014)
The effect of syringyl:guaiacyl (S/G) ratio on kraft pulping and kraft pulping followed by O-2 delignification was investigated with six poplars grown on the same site. The results showed an improvement in the ease of delignification (EOD) when the S/G ratio was increased from a low to a moderately high value. However, above that moderately high value there was no further improvement in EOD with increasing S/G ratio. Kraft pulping followed by elemental chlorine-free (ECF) bleaching was then investigated with three Brazilian eucalypti with S/G ratio of 2.69, 2.46 and 2.41. The chips with S/G = 2.69 had superior EOD compared to the chips with S/G = 2.41. However, pulps from the S/G = 2.69 chips also contained less lignin-carbohydrate complexes (LCC) than corresponding pulps from the chips with S/G = 2.41. LCC are known to retard delignification in both alkaline pulping and ECF bleaching. The S/G ratio of eucalyptus pulp lignins was estimated by nitrobenzene oxidation (NBO) of the pulps and H-1 NMR or their isolated lignins. The S/G ratio decreased from a value of >= 2.46 for the lignin in two eucalyptus chip samples to <= 1.21 for the lignin in their kraft pulps. In general, S units appear to solubilize at a much higher rate than G units during kraft pulping.
Keywords: Hardwood; S/G ratio; lignin-carbohydrate complexes; kraft pulping; ECF bleaching